2022
DOI: 10.1002/jmr.3003
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the interaction between the kusaginin and bovine serum albumin: Multi‐spectroscopic techniques and computational approaches

Abstract: Kusaginin, as a phenylethanoid glycoside, which has exhibited wide antioxidant and antimicrobial properties. The molecular mechanism underlying the broad biological activities of kusaginin has not yet been well documented. In this paper, the interaction of kusaginin with bovine serum albumin (BSA) has been explored by fluorescence spectra, UV‐vis absorption spectra, and circular dichroism (CD) spectra along with computational approaches. The fluorescence experiments showed that kusaginin could strongly quench … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…Therefore, some involvement of ground state complex formation (static mechanism) can also be assumed in the quenching process. Hence, there arises a possibility of involvement of mixed quenching phenomena 34–36 . Thus, we have employed the modified Stern–Volmer equation (equations S1, S2, S3) for mixed quenching and observed that at all five temperatures (298, 303, 308, 313 and 318 K) the plots (Figure S3) result in the slope (K D .K S ) as 7.053, 12.759, 18.176, 19.351 and 22.345 × 10 8 M −2 , respectively.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, some involvement of ground state complex formation (static mechanism) can also be assumed in the quenching process. Hence, there arises a possibility of involvement of mixed quenching phenomena 34–36 . Thus, we have employed the modified Stern–Volmer equation (equations S1, S2, S3) for mixed quenching and observed that at all five temperatures (298, 303, 308, 313 and 318 K) the plots (Figure S3) result in the slope (K D .K S ) as 7.053, 12.759, 18.176, 19.351 and 22.345 × 10 8 M −2 , respectively.…”
Section: Resultsmentioning
confidence: 98%
“…The interaction affected some of the inner stabilizing forces resulting in the alteration of the secondary helical structure of BSA. These changes may be due to alteration of the hydrophobic pocket caused by disruption of hydrogen bonding upon binding with hydrophobic SEL, thus there is a change in polarity of the microenvironment of the hydrophobic cavity upon binding which resulted in a significant decrease in α ‐helix content 34,61 …”
Section: Resultsmentioning
confidence: 99%
“…Estimated values of K b were in the order of 10 7 M − 1 indicating the signi cant binding between lanosterol and BSA. Values of K b were shown to increase might be due to the enhanced stability of complex with rise in temperature [31].…”
Section: Binding Parameters Of Lanosterol-bsa Complexesmentioning
confidence: 93%
“…The transport proteins, serum albumins, HSA and BSA, are also explored for their interactions with drugs and other molecules. Huang et al carried out BSA interaction studies with a glycoside kusaginin 21 . Similarly, Zhu et al, ascertained interaction mechanism as well as the conformational changes in the serum albumins on binding with the drugs artemisinin and dihydroartemisinin 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al carried out BSA interaction studies with a glycoside kusaginin. 21 Similarly, Zhu et al, ascertained interaction mechanism as well as the conformational changes in the serum albumins on binding with the drugs artemisinin and dihydroartemisinin. 22 Khan et al studied the binding mechanism between BSA and topiramate.…”
mentioning
confidence: 99%